Pengelolaan Pembelajaran Kelas Inklusi di SDN Ronggo 03 Kecamatan Jaken Kabupaten Pati - Roni, Ahmad Yusuf, Dr. Eko Supriyanto,S.H.,M.H, Dr. Sumardi, M.Si (2015)
The pupose of this research is to describe the planning, the implementation, and the evaluation of the management process of inclusive learning at SDN Ronggo 03 Jaken Subdistrict Pati Regency. Method of the research is qualitative naturalistic, because it was done in naturalistic condition. On it ignored to the similiarity of the research's objects but on contrary to reveal some different people view of life. The result of the research showed: 1. Learning plan prepared well by teachers based on the existing curriculum with a form of development in accordance with the class inclusion, create a syllabus and lesson plans to guide the learning process, 2. Refers to the implementation of learning based on existing plans and the implementation went quite well, 3. Evaluation of the learning is done by teachers include program evaluation, evaluation of the learning process and the evaluation of student learning outcomes. However there are some constraints, especially in terms of teacher qualifications that no special teacher ABK, the lack of assistance from specialized services and infrastructure that support. The conclusion that Ronggo SDN 03 was not called as a school inclusion, but in its management already contains inclusions of learning. Keywords: management, learning, inclusion